Changes and challenges of the archives: researching early-twentieth century lesbianism in United States prisons during the COVID-19 pandemic. Issue 4 (2nd October 2021) - Wegener, Sidney
ABSTRACT: "Changes and Challenges of the Archives" is based on a still-in-progress master's thesis that I will complete by May 2021 at Sarah Lawrence College. The purpose of this article is not to come to any conclusions about the challenges of researching lesbian history during the COVID-19 pandemic but, rather, to explore how these world circumstances have further complicated the labor required of a lesbian historian. Many elements of this thesis and research are still in flux, including my investigation of the role race played in creating and developing a sexually deviant, criminalized definition of lesbian(ism). My ultimate hope is that this paper provides some valuable knowledge for my queer historian comrades and sparks a dialogue that can benefit historians who are continuing their research through debilitating circumstances.